Avaliação da síndrome consumptiva em pacientes internados com HIV/AIDS - ALEIXO, Brenda Cristina Pinheiro (2023)
The present descriptive, cross sectional, cross sectional study aimed to identify the consumption syndrome and to define the anthropometric profile of patients hospitalized with HIV / AIDS of both sexes, aged 20 years or older. Subjected to the analysis of the anthropometric evaluation, sociodemographic profile, from the assessment sheet of the Extension Project titled "Nutrition Monitoring of Inpatients in the Clinic of Infectious and Parasitary Diseases of the HUJBB" developed from March 2017 to February 2018. For the preparation of the study, anthropometric measurements were used: current weight (BP), usual weight (PU), height, arm circumference (CB), body mass index (BMI), percentage of CB and PU adjustments), used for the definition of nutritional diagnosis. The majority of patients presented a weight loss compatible with the classification of the consumptive syndrome. Thus, through the nutritional screening, it was possible to identify that the majority of the patients evaluated were at nutritional risk. The information found indicates the need for the early introduction of nutritional monitoring in the prevention and / or treatment of malnutrition in order to reduce HIV complications, improving the effectiveness of drug therapy, reducing hospitalization time and allowing progress in the quality of life of the patients with HIV / AIDS.